Parasagittal Approach of Epidural Steroid Injection as a Treatment for Chronic Low Back Pain: A Systematic Review and Meta-Analysis - Knezevic, Nebojsa Nick; Paredes, Stephania; Cantillo, Santiago; Hamid, Albara; Candido, Kenneth D. (Frontiers in Pain Research, 2021)
Background: Epidural steroid injection (ESI) has proven benefits in controlling chronic low back pain and can be performed via the midline interlaminar (MIL) or transforaminal (TF) approach. A modified interlaminar approach, the parasagittal interlaminar (PIL), has surfaced as a more reliable, safe, and suitable approach to minimize complications related to MIL and TF. Objective: To conduct a systematic review and meta-analysis to assess and compare the effectiveness and safety of PIL with both MIL and TF approaches in adult patients with a history of chronic low back pain. Methods: A literature search was conducted using major electronic databases, such as PubMed, EMBASE, and Cochrane. Selected studies included patients with unilateral radicular symptoms, secondary to lumbar intervertebral disc hernias or degenerative lumbar disc disease, that, additionally, received ESIs via PIL or either MIL or TF under fluoroscopic guidance. Randomized and observational studies with pain relief score and/or functional disability assessment and at least a 2-week follow-up were included. Results: The search led to the initial identification of 174 studies. Following the screening, eight studies were included in the qualitative analysis and seven randomized controlled trials (RCTs) were included in the statistical analysis. PIL showed statistically significantly more pain relief and functional improvement than MIL at 1-, 3-, and 6-month post-procedure. Compared to TF, PIL showed statistically significantly more pain relief at 3- and 6-month after the procedure. Additionally, PIL showed benefits in terms of lower mean fluoroscopy time, less radiation exposure, zero adverse events in all the included studies, no cases of intravascular spread compared with the TF approach, and a higher anterior epidural spread (AES) of PIL compared with TF. Conclusions: Our systematic review and meta-analysis suggest that the PIL approach is an effective and safe alternative to the MIL and TF approaches in patients presenting with chronic low back pain when epidural injections are indicated, demonstrating a higher level of pain relief and a stronger improvement in functionality post-procedure.